Geographic Information System for Tsunami Disaster Mitigation Evacuation Routes Moving the Sunda Subduction Megathrust (Case Study: Analysis of Pangandaran Regency) - Harahap, Parlindungan; Sapanji, R. A. E. Virgana Targa; Nugraha, Ucu (Journal of Applied Geospatial Information, 2023)
Pangandaran Regency has the potential for an earthquake disaster accompanied by a tsunami which occurred on July 17 2006 at 15.19 with a magnitude of 7.7, earthquake data from the USGS shows an earthquake of magnitude 5-9, there are 909 earthquake points between 1918 - 2023, 2 earthquake points above magnitude 7 (7.7 and 7.44), 18 earthquake points above magnitude 6-6.9, below magnitude 6 there were 887 earthquake points, earthquake points in the south of Pangandaran Regency were concentrated between 2 groups of locations. Raster calculation of land surface at 5 meters above sea level and 10 meters above sea level is not recommended as a location to escape for tsunami disaster mitigation, also 20 meters above sea level is not recommended unless there are no other higher areas, 30 meters above sea level is highly recommended with a note if there are higher areas it is better to shift to a higher area, because tsunami waves cannot be predicted when they hit one area, their height can be different when they hit another area, it can be calculated that the potential impact of the tsunami disaster is 90,576 buildings or houses. Several villages could be rescue locations to mitigate potential tsunami disasters in Pangandaran Regency, such as in Cimerak sub-district (Limusgede village and Cimerak village), in Cijulang sub-district (Kertayasa village and Margacinta village), in Parigi sub-district (Parakanmanggu village, Cintakarya village, Selasari village), in Sidamulih subdistrict (Kersaratu village and Kalijati village), in Pangandaran subdistrict (Pagergunung village), in Kalipucang subdistrict (Ciparakan village), in Padaherang subdistrict (Payutran village, Bojongsari village, Karangsari, Kedangwuluh, Pasirgeulis), for Mangunjaya subdistrict all areas in below 30 meters so that mitigation locations must be prepared in several border villages in Ciamis Regency.